The Performance Effectiveness of the Kamsel Unit Through Traffic Dikmas to Reduce Traffic Violations in the Jurisdiction of the Tuban Police (Advances in Police Science Research Journal, 2024)
Traffic violations are rampant in Indonesian society, including in Tuban Regency. To enforce discipline among unruly drivers, the police not only apply legal measures (fines) but also educational actions. Educational activities in Tuban Regency are conducted through Traffic Community Education (Dikmas Lantas) by the Traffic Control Unit of Tuban Police Resort. This research aims to describe the organizational resources of the Traffic Control Unit of Tuban Police Resort and the management system of Dikmas Lantas activities to reduce traffic violations. The research method used is a qualitative approach with field research methods, using primary and secondary data sources. Data collection techniques include interviews, observations, and document studies, with data validity using triangulation. Based on the research results, it was found that there are internal factors hindering the process, including lack of personnel and their quality, facilities, infrastructure, and limited budget. External factors include lack of public awareness to comply with traffic regulations.
Keywords: Efektivitas; pelanggaran lalu lintas; Dikmas lantas; kinerja